Dynamic response characteristics of the initial support structure of the double-track tunnel blasting - HUANG Chuansheng; YANG Xin; LIN Jihua; XU Hao; HU Deyu; REN Kaifu (Shenzhen Daxue xuebao. Ligong ban)
In the process of blasting excavation of the later excavated tunnel, it is crucial to ensure the safety of blasting vibration in the first excavated tunnel. Using the blasting excavation of the Zimuyan Tunnel in Guizhou, China, as the engineering background, we analyze the attenuation law of vibration velocity peak of the left and right lines and the stress distribution characteristics based on the field monitoring and numerical simulation methods. The safety threshold of the blasting vibration velocity is also proposed. The results show that during the blasting of the later-excavated tunnel, the maximum vibration velocity of the initial support of the later excavated tunnel occurs at the vault and the arch waist, with faster attenuation at the vault. In the first-excavated tunnel, the maximum vibration velocity of the initial support structure occurs at the side arch waist of the blasting surface, and the vibration velocity peak sequence on the blasting surface is left arch waist > left arch foot > vault, with the maximum vibration velocity at the blasting surface being approximately four times that of the back blasting surface. The attenuation law of vibration velocity of the first excavated tunnel is similar to that of the later excavated tunnel, with the fastest attenuation at the vault, followed by the arch waist. The vibration velocity peak and stress distribution of the initial support structure of the first-excavated tunnel are symmetrically distributed based on the excavation surface. Additionally, a safety-judging standard based on vibration velocity peak and tensile stress is established. It is concluded that the safe velocity for liner structures is 10.81 cm/s, with the maximum single-stage charge amount determined to be 58.2 kg. The research provides a reference for the safe construction of tunnels when excavating double-line tunnels simultaneously.